Case report: Infantile generalized pustular psoriasis with IL36RN and CARD14 gene mutations - Tong, Xinyun; Li, Yang; Tang, Xianfa; Ding, Yantao; Sun, Yao; Zheng, Liyun; Pan, Yulong; Liu, Shengxiu (Frontiers in Genetics, 2023)
Infantile pustular psoriasis (IPP) is an extremely rare skin disease associated with genetic factors. Gene mutations of IL36RN, CARD14 and AP1S1 had been identified to be involved in pathogenesis of IPP. Compared with adult patients, children usually developed with IPP with no preceding PV or familial history and prone to detect gene mutations as mentioned above. Here we report a case of 6-month-old infant and make the diagnosis of IPP by series of examinations, subsequently by detecting coexistent mutations of IL36RN and CARD14, the diagnosis is intensified from genetic point of view. We treated the child with traditional oral and topical drugs regardless of well-known acitretin considering it’s potential side effects, such as skeletal toxicity, the lesions got conspicuous improvement as well as reduction of inflammatory levels. Owing to genetic mutation of IL-36, there had been reported cases focusing on anti-IL36 biological agents to apply in treating IPP, it could be a new weapon to treat and improve such IL-36RN deficient skin diseases. Key words：Infantile pustular psoriasis, gene mutation, IL36RN, CARD14, AP1S1, biological agents.